The Role of Investment-Based Islamic Crowdfunding for Halal MSMEs: Evidence from Indonesia - Abdullah, Zaki; Susamto, Akhmad Akbar (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2019)
Investment-based crowdfunding can serve as an alternative financing tool for Micro, Small and Medium Enterprises (MSMEs) in Indonesia. The development of these services can also boost the progress of halal industry because both have integrated relationships. However, not all funding campaigns for crowdfunding services are successful. This study aims to analyze the development of Islamic crowdfunding business in Indonesia and factors affecting the success of funding campaigns in these services. Primary data obtained through interviews and literature review while secondary data is collected from 39 funding campaigns in 4 Islamic crowdfunding online services. Using a quantitative approach, it finds that funding target, campaign duration, payback periods and rate of return have positive effects on campaign success, while a minimum amount of investment has a negative effect. Finally, SWOT analysis was conducted to find out the challenges and opportunities for the halal industry in utilizing such Islamic crowdfunding service. Abstrak:Crowdfunding berbasis investasi dapat menjadi sarana pembiayaan alternatif bagi UMKM di Indonesia. Berkembangnya layanan tersebut turut mendorong kemajuan industri halal karena keduanya memiliki hubungan yang terintegrasi. Namun, tidak semua kampanye pendanaan pada layanan crowdfunding berhasil. Penelitian ini bertujuan untuk menganalisis perkembangan usaha crowdfunding syariah dan faktor-faktor yang mempengaruhi keberhasilan pendanaan pada layanan tersebut. Data primer diperoleh melalui metode wawancara dan kaji literatur sedangkan data sekunder diperoleh melalui 39 kampanye pendanaan pada 4 situs crowdfunding syariah. Target pendanaan, durasi kampanye, jangka waktu pengembalian dan tingkat bagi hasil memiliki pengaruh positif terhadap keberhasilan kampanye, sementara jumlah investasi minimal memiliki pengaruh negatif. Setelah melakukan penelitian dengan pendekatan kualitatif dan kuantitatif, analisis SWOT dilakukan untuk mengetahui tantangan dan peluang bagi industri halal dalam memanfaatkan layanan crowdfunding.